The dynamics of root cap sloughing in Arabidopsis is regulated by peptide signalling - Shi, Chun-Lin; Von Wangenheim, Daniel; Herrmann, Ullrich; Wildhagen, Mari; Kulik, Ivan; Kopf, Andreas; Ishida, Takashi; Olsson, Vilde; Anker, Mari Kristine; Albert, Markus; Butenko, Melinka A.; Felix, Georg; et al. (Nature Plants, 2018)
The root cap protects the stem cell niche of angiosperm roots from damage. In Arabidopsis, lateral root cap (LRC) cells covering the meristematic zone are regularly lost through programmed cell death, while the outermost layer of the root cap covering the tip is repeatedly sloughed. Efficient coordination with stem cells producing new layers is needed to maintain a constant size of the cap. We present a signalling pair, the peptide IDA-LIKE1 (IDL1) and its receptor HAESA-LIKE2 (HSL2), mediating such communication. Live imaging over several days characterized this process from initial fractures in LRC cell files to full separation of a layer. Enhanced expression of IDL1 in the separating root cap layers resulted in increased frequency of sloughing, balanced with generation of new layers in a HSL2-dependent manner. Transcriptome analyses linked IDL1-HSL2 signalling to the transcription factors BEARSKIN1/2 and genes associated with programmed cell death. Mutations in either IDL1 or HSL2 slowed down cell division, maturation and separation. Thus, IDL1-HSL2 signalling potentiates dynamic regulation of the homeostatic balance between stem cell division and sloughing activity.
CRIS-Team Scopus Importer:2020-03-09